Teaching Tolerance through Law and Language: English for Sharia Purposes and Interfaith Legal Education in Indonesia - Saputra, Heru; Sakhiyya, Zulfa; Astuti, Puji; Rozi, Fahrur; Masyhar, Ali; Paudel , Dolendra (Contemporary Issues on Interfaith Law and Society, 2025)
This study examines how English for Sharia Purposes can serve as a pedagogical platform for cultivating tolerance and interfaith competence among Muslim law students in Indonesia’s plural legal order, where state law interacts with Sharia-based norms and diverse religious communities. Conducted at Universitas Islam Negeri (UIN) Salatiga within the Constitutional Law study program of the Faculty of Sharia, the research responds to institutional commitments to Islamic moderation and global engagement. While English for Specific Purposes (ESP) in Sharia faculties has traditionally emphasized linguistic proficiency, limited attention has been given to its potential for preparing future Sharia lawyers to navigate socio-legal challenges involving religious rights, minority protections, and interreligious dispute resolution. Using a qualitative descriptive design, data were collected through classroom observations, semi-structured interviews with lecturers and students, and document analysis of teaching materials and institutional policy statements. Findings show that debates on minority rights, interfaith-mediation role-plays, and analysis of constitutional and international human-rights texts did more than improve students’ legal English; they fostered professional dispositions of fairness, empathy, and rights-aware reasoning grounded in Sharia principles of ʿadl (justice), tasāmuh (tolerance), and wasatiyyah (moderation). Student reflections suggested movement from “othering” to recognizing non-Muslims as equal subjects of justice, consistent with intercultural sensitivity and interfaith competence models. The study contributes to interfaith law and society by demonstrating how discipline-specific language education can serve as a socio-legal formation, translating interfaith ethics into practical legal communication skills for plural, rights-based contexts.